After the end of multiculturalism: Public service media and integrationist imaginaries for the governance of difference. (December 2014) - Titley, Gavan
This article assesses the public service media (PSM) 'turn to diversity' in several European contexts and examines the ways in which this emerges from a rejection of multiculturalism that is at once politically sustained and analytically inchoate. It approaches PSM as national institutions conditioned to mediate coherent images of society. In contemporary European societies, this positions PSM in a field in which integrationist imaginaries of the nation are insistent, but under conditions of social complexity, which render homogeneous visions of the nation difficult to mediate. In this context, diversity has developed as a framework for mediating, and being held to mediate, lived multiculture. However, recent research suggests that this shift to diversity both depoliticizes the 'politics of difference' and may also further the prevalent integration politics currently in the ascendant in Western Europe.